A Systematic Mapping Study of the Empirical MOOC Literature - Rasheed, Rasheed Abubakar; Kamsin, Amirrudin; Abdullah, Nor Aniza; Zakari, Abubakar; Haruna, Khalid (Institute of Electrical and Electronics Engineers, 2019)
Massive open online courses (MOOCs) have revolutionized todays education by offering a global accessible form of online learning. Over the years, MOOCs have been an attractive research area and have yielded an ample amount of research publications. However, the existing review studies in MOOCs are characterized by short year coverage or focusing on a specific theme. As such, a systematic mapping methodology was adopted to provide a fine-grain overview of MOOC research domain by identifying the quantity, types of research, available results and publication trends in educational aspects of MOOCs from 2009 to 2018. Key findings show that I) MOOC research have been on the rise since MOOCs became mainstream in 2011. II) MOOC research largely resides in the United States and few European countries. II) Most of MOOC studies focused on addressing learners' completion/dropout/retention. In addition, we proposed some recommendations for future research on MOOCs. © 2013 IEEE.